The onset of the Paleocene-Eocene Thermal Maximum (PETM) at Sites 1209 and 1210 (Shatsky Rise, Pacific Ocean) as recorded by planktonic foraminifera - M.R. Petrizzo (Marine Micropaleontology, 2007)
High-resolution biostratigraphic and quantitative studies of subtropical Pacific planktonic foraminiferal assemblages (Ocean Drilling Program, Leg 198 Shatsky Rise, Sites 1209 and 1210) are performed to analyse the faunal changes associated with the Paleocene–Eocene Thermal Maximum (PETM) at about 55.5 Ma. At Shatsky Rise, the onset of the PETM is marked by the abrupt onset of a negative carbon isotope excursion close to the contact between carbonate-rich ooze and overlying clay-rich ooze and corresponds to a level of poor foraminiferal preservation as a result of carbonate dissolution. Lithology, planktonic foraminiferal distribution and abundances, calcareous plankton and benthic events, and the negative carbon isotope excursion allow precise correlation of the two Shatsky Rise records. Results from quantitative analyses show that Morozovella dominates the assemblages and that its maximum relative abundance is coincident with the lowest δ13C values, whereas subbotinids are absent in the interval of maximum abundance of Morozovella. The excursion taxa (Acarinina africana, Acarinina sibaiyaensis, and Morozovella allisonensis) first appear at the base of the event. Comparison between the absolute abundances of whole specimens and fragments of genera demonstrate that the increase in absolute abundance of Morozovella and the decrease of Subbotina are not an artifact of selective dissolution. Moreover, the shell fragmentation data reveal Subbotina to be the more dissolution-susceptible taxon. The upward decrease in abundance of Morozovella species and the concomitant increase in test size of Morozovella velascoensis are not controlled by dissolution. These changes could be attributed to the species'' response to low nutrient supply in the surface waters and to concomitant changes in the physical and chemical properties of the seawater, including increased surface stratification and salinity. Comparison of the planktonic foraminiferal changes at Shatsky Rise to those from other PETM records (Sites 865 and 690) ...